Folic acid supplementation ameliorates alcohol-induced hepatic steatosis by inhibiting SREBP-1c-mediated lipogenesis - Liang, Chen; Sun, Hao; Lan, Tongtong; Yin, Junlei; Zhao, Huichao (Frontiers in Nutrition, 2025)
BackgroundAlcoholic fatty liver disease (AFLD), a prevalent yet reversible stage of alcoholic liver pathology, is often associated with folate deficiency. This study investigated the association between folate status and AFLD risk and explored the underlying mechanisms.MethodsData from NHANES 2011–2020 (n = 10,452; 259 with AFLD) were analyzed. Associations between dietary folate equivalent (DFE), serum folate, 5-methyltetrahydrofolate (5-MTHF), red blood cell (RBC) folate, and AFLD were evaluated using multivariable logistic regression, adjusting for demographic and clinical variables. In parallel, ethanol-fed C57BL/6J mice, with or without folic acid supplementation, and L02 hepatocyte models were used to assess biochemical markers, hepatic histology, and lipogenesis-related protein expression.ResultsHigher serum folate levels were significantly associated with reduced AFLD risk across all adjusted models (Model 3 Q4 vs. Q1, OR = 0.35, 95% CI: 0.22–0.54). Serum 5-MTHF levels were inversely associated with the severity of steatosis (p < 0.01). In contrast, elevated RBC folate was a risk factor in specific subgroups. Folic acid intervention in vivo/in vitro reduced ethanol-induced increases in hepatic enzymes, TG, hepatic lipid accumulation, and expression of lipogenic proteins (SREBP-1c, FASN, ACC1; p < 0.05), but not SCD-1.ConclusionSerum folate and 5-MTHF are protective factors against AFLD. Furthermore, folic acid can ameliorate hepatic steatosis by inhibiting SREBP-1c-mediated lipogenesis, highlighting its potential in AFLD prevention and therapy.